THE NEIGHBORHOOD IS IN(CLUSIVE): LEVERAGING CO-DESIGN FOR COMMUNITY EMPOWERMENT - Cardoso, Ana (Design/Arts/Culture, 2025)
This study explores the intersectionality of Design for Aging, Health and Well-being, and Social Design within the intricate socio-cultural ecosystems of local communities. It underscores the efficacy of participatory design and artistic practices as instrumental mechanisms in fostering collaborative creativity and addressing collective societal challenges. Emphasis is placed on the pivotal role of university-level students in enhancing socio-political interventions, thereby positioning them as vital advocates for social justice and community empowerment. This research is exemplified through the case study of "The Neighborhood is IN(clusive)" project, spearheaded by ESAD—College of Art and Design, and funded by the Healthy Neighborhoods Program, focusing on the Cruz de Pau neighborhood in Matosinhos, Portugal.